(untitled) (The Journal of Geography Education in Africa, 2022)
One of the challenges related to the teaching and learning of weather and climate in the social sciences is the somewhat abstract nature of these concepts. Incorporating indigenous knowledge (IK), a form of prior knowledge that learners acquire from communities and passed down through generations, can assist in making learning meaningful and relevant. Using a qualitative research design, we firstly explore the type of IK related to weather and climate practiced in a local rural community to identify the overlapping knowledges of community elders and Grade 5 social sciences teachers. Secondly, we set out to determine how these teachers view the incorporation of IK in the teaching of weather and climate. Finally, we show how teachers perceive the relationship between IK and scientific knowledge.The data confirms that there is a shared awareness, among the community members and teachers, of the rituals and practices associated with weather and climate in this area. Teachers do see the value of integrating IK into the lessons pertaining to weather and climate in their primary school classroom as it allows them to activate learners’ prior knowledge and connects the classrooms to the communities from which the learners come. The data shows that teachers largely support the blending of IK with scientific knowledge in their classrooms in order both to activate prior knowledge and to address misconceptions. It is therefore important to create constructivist learning environments in classrooms that encourage debate and dialogue and which do not pitch IK and scientific knowledge against one another.